2016
DOI: 10.1590/s1519-99402016000400010
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trait and repeatability models for genetic evaluation of litter traits in pigs considering different farrowings

Abstract: SUMMARYWe aimed to compare multi-trait and repeatability models to estimate genetic parameters for the traits number of piglets born alive (NBA) and alive at 3 week of age (NP3), litter weight at birth (LW0) and at 3 week of age (LW3), and mean piglet weight at birth (MW0) and at 3 week of age (MW3), considering the first three farrowings of Landrace sows. Heritability (h 2 ) estimates showed an increasing pattern up to the third farrowing for LW0 and MW3. For NBA, NP3, LW3, and MW0 h 2 increased from the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Although Irgang, Fávero, and Kennedy () and Noguera et al () found that the heritability increased with increasing parity number, the results observed in this study were essentially opposite. The heritability across parities in this work showed no trend with the increasing number of parity, which corroborates with the prior studies of Alfonso, Noguera, Babot, and Estany () and Costa et al ().…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Although Irgang, Fávero, and Kennedy () and Noguera et al () found that the heritability increased with increasing parity number, the results observed in this study were essentially opposite. The heritability across parities in this work showed no trend with the increasing number of parity, which corroborates with the prior studies of Alfonso, Noguera, Babot, and Estany () and Costa et al ().…”
Section: Resultssupporting
confidence: 93%
“…Overall, heritability estimates analyzed using a multi‐trait model for each trait at different parities were found to be higher than those in the repeatability analyses of both breeds, which might be explained by the simplicity of the model. Costa et al () who also compared the multi‐trait and repeatability models used for genetic evaluations of litter traits in Landrace pigs for different farrowings reported that the estimated heritability in the repeatability model was lower than the mean of the estimates in the multi‐trait model. The heterogeneity of heritability observed in this study suggests that different parities should be considered as different traits, which is also in agreement with the results of Fernández et al ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have confirmed that genetic progress in the overall reproductive performance of sows can be most effectively achieved by selection for litter size [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Postnatal litter size can be described as the NBA, stillborn, total born and weaned piglets.…”
Section: Introductionmentioning
confidence: 99%